Modeling and simulation of logistics flows 3 - Réveillac, Jean-Michel (ISTE Ltd/John Wiley & Sons, 2017)
Volume 3 begins with an introduction to which are added four chapters focused on modeling and flow simulation in an environment in 2 or 3 dimensions (2D or 3D). They deal with different cases taken from situations found in the field. A conclusion comes close this third book: The different software used in this third volume. Computer simulation of discrete flows. Mixed flow simulation. Flows in 3D and the evacuation simulation. Flows in 3D for conveying and storage. The conclusion discusses the future developments of the software and their integration into society. At the end of each volume is a bibliography and a list of web links. There is also a glossary explaining some abbreviations, acronyms and some very specific terminology of logistics and operations research.